Healthy lives: Tackling food-borne diseases and zoonoses - Grace, Delia; Roesel, Kristina; Bett, Bernard K.; Unger, Fred (International Livestock Research Institute, 2014)
The International Livestock Research Institute (ILRI) was created in the early 1990s, and, like CGIAR crop centres, its major goal was increasing productivity. Animal health was believed to cause about one-fourth of the yield gaps seen in developing countries, but almost all research centreed on just two diseases thought to have greatest impacts on productivity: trypanosomosis and East Coast fever. Human health impacts were explicitly not a priority. By 2000 ILRI began actively to address zoonoses, but only in the context of their threat to intensifying smallholder production. By 2004, human health was an objective in its own right and the first research programme dedicated to zoonoses and food safety at ILRI began in 2011. During the period of increasing focus on the human health implications of smallholder livestock production, some major research achievements were made, including: the first pro-poor ranking of zoonoses research priorities; reliable assessments of milk safety in Kenya’s informal markets; use of participatory disease surveillance methods for avian influenza; applications of risk-based approaches to food safety in informal markets; development of new diagnostic tests for pig tapeworm; a global mapping of poverty and zoonoses; and deployment of a decision-support tool for control of Rift Valley fever. Evidence generated over the last decade and a half shows the three most important livestock-associated human health problems are food-borne disease, emerging infectious disease, and nutritional problems associated with eating too much or too little animal-source food. Current research on these topics by ILRI and partners extends from upstream projects hunting for viruses and generating vaccines, to the development, marketing and testing of diverse livestock technologies, to piloting practical approaches to disease surveillance and control in resource-scarce environments.